Effect of Lockdown on Unemployment Empirical Studies on Bekasi and Bogor - Hudi, Mokh Firdaus Alam (Jurnal Ekonomi Dan Statistik Indonesia, 2025)
COVID-19, which began in early 2020, had an effect on various sectors, including an impact on the economies of many countries in the world and caused a recession in many countries in the world. The Indonesian government implemented a lockdown or PSBB to reduce the impact of COVID-19. This also impacts the Unemployment Rate. This study analyzes the impact of Lockdown on the Unemployment Rate with case studies in Bekasi and Bogor. Using Sakernas data from August 2019 and August 2020 and the Synthetic Control Method and DiD methods, the results show that the implementation of the PSBB in Bekasi Regency has a negative effect on individual work status of 0.1441 with a significance of 1%. In Bekasi City, the results obtained from the implementation of the PSBB are negative for individual work status of 0.155 with a significance of 1%. Meanwhile, in Bogor Regency and City, the results were not significant.